2017
DOI: 10.1182/bloodadvances.2017006809
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of BCR signaling inhibitors in immunomodulation of chronic lymphocytic leukemia

Abstract: Approved therapies that target the B-cell receptor (BCR) signaling pathway, such as ibrutinib and idelalisib, are known to show activity in chronic lymphocytic leukemia (CLL) via their direct effects on crucial survival pathways in malignant B cells. However, these therapies also have effects on T cells in CLL by mediating toxicity and possibly controlling disease. By focusing on the effects of BCR signaling inhibitors on the T-cell compartment, we may gain new insights into the comprehensive biological outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 95 publications
(91 reference statements)
0
17
0
Order By: Relevance
“… 11 Besides its direct cytotoxic activity against malignant B cells, ibrutinib also exerts immunomodulatory effects (reviewed by Maharaj et al .). 12 Ibrutinib-mediated inhibition of STAT3 results in decreased expression of immunosuppressive molecules, such as PD-L1 and IL-10, by CLL cells. 13 Gunderson et al .…”
Section: Introductionmentioning
confidence: 99%
“… 11 Besides its direct cytotoxic activity against malignant B cells, ibrutinib also exerts immunomodulatory effects (reviewed by Maharaj et al .). 12 Ibrutinib-mediated inhibition of STAT3 results in decreased expression of immunosuppressive molecules, such as PD-L1 and IL-10, by CLL cells. 13 Gunderson et al .…”
Section: Introductionmentioning
confidence: 99%
“…cytotoxic potential. Quantification of these populations based on xshift analysis demonstrated that some clusters with cytotoxic potential (6,9,10,11,12) appeared enriched in treatment groups ( Figure S5B). The expression distribution of each marker in the tSNE plot is shown in Figure S6.…”
Section: Combination Of Hdac6 Inhibition and Pd-1/pd-l1 Blockade Augmmentioning
confidence: 99%
“…Based on these observations, it has been postulated that reversal of T-cell dysfunction may restore Tcell mediated antitumor activity. Detailed reviews of CLL T-cell dysfunction can be found here (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ibrutinib treatment leads to an immediate downregulation of a plethora of chemokines in the plasma, mainly through alteration of CLL cells and TME cells in the lymph nodes [157]. The immunomodulatory effects of BCR signaling inhibitors has recently been reviewed by Maharaj et al [158]. Interestingly, IL-4 expression increases surface IgM expression and reduces CXCR4 and CXCR5 and seems to render CLL cells resistant to BCR-signaling inhibitors ibrutinib and idelalisib [159].…”
Section: Immune Cells In the Tumor Microenvironmentmentioning
confidence: 99%